Pengaruh Konsentrasi Pemberian Urine Sapi Fermentasi Terhadap Pertumbuhan Stek Tebu (Saccharum officinarum L.) Single Bud - Didin Dianarafah; M. Badri Burhan; Widodo Saputra (Universitas Islam Malang, 2023)
The bud chip nursery technique is a nursery with one bud which is commonly used in sugarcane. The purpose of this study was to determine the effect of the concentration of fermented cow urine on the growth of single bud sugarcane (Saccharum officinarum L.) cuttings. This study used a randomized block design experiment (RAK) with 5 replications and 5 treatment levels, namely: P0 = without giving fermented cow urine concentration; P1 = Concentration of 25% fermented cow urine; P2 = Concentration of 20% fermented cow urine; P3= Concentration of fermented cow urine 75%; and P4 = Concentration of 100% fermented cow urine. Testing data with Polynomial Orthogonal Test. The results of this study indicate that the concentration of fermented cow urine has a significant effect on the growth of sugarcane cuttings. The higher the concentration of fermented cow urine given, the better the growth of sugarcane cuttings on the variable number of leaves, root length, fresh weight of roots, fresh weight of shoots, and dry weight of shoots. However, giving various concentrations of cow urine did not affect the variable percentage of sprouted cuttings.